Horizon Scanning for Emergence of New Viruses: From Constructing Complex Scenarios to Online Games. Issue 5 (5th July 2012) - Gale, P.; Breed, A. C.
Summary: Horizon scanning techniques can be developed to identify novel routes and sources for the emergence of viruses in the medium to long term. Central to horizon scanning is prediction of the complex scenarios through which viruses could emerge before they occur. One approach involves 'spidergrams' in which complex scenarios are generated by combining factors randomly selected from different categories of events. Spidergrams provide a framework for how different factors could interact, irrespective of the virus, and also enable testing of combinations not previously considered but which would be 'tested' in nature by a virus. The emergence of viruses through new routes is often related to changes, for example, in environmental and social factors, and the Internet will undoubtedly be used to identify long‐term trends for consideration. In addition, online games may provide horizon scanners with suggestions for new routes and strategies that could be used by emerging viruses.